Avaliação cognitiva breve em pessoas com comportamentos aditivos - Robalo, Mariana da Silva (2016)
Theoretical Background: The addictive behaviour is characterized by an apparent loss of control and autonomy in the person’s behaviour. In the neuropsychology study centred in the dependence of drugs there are still many question in open discussion. Different studies still show very diverse results in relation to the neuropsychological consequences in drug addicts. Thus, the directional question of the present study can be posed in the following terms: are there cognitive impairments associated to psychoactive substance abuse behaviours? If so, is a brief cognitive evaluation informative of the mentioned impairments? Methodology: The sample of the present work consisted in 42 participants, with age comprehended between 20 and 59 years old. Representing a convenience sample, of a population with very specific clinic and psychosocial characteristics – person with addictive behaviours. It was applied MoCA and a set of tests, testing the 5 domains of cognitive evaluation: Memory, Visuospatial Ability, Language, Attention and Executive Function Ability. Results: The results of the tests prove the existence of cognitive impairments in individuals with psychoactive substances and alcohol abuse behaviours. Of the 42 individuals of the sample, 39 accused to have impairments in the set of tests and 30 accused to have impairments in MoCA. Assuming as real the results of the set of tests, 90% (n=27) of the impairments noted by MoCA were correct and the remaining 10% (n=3) of the impairments noted by MoCA were false. On its turn, MoCA identified as not having an impairment 12 individuals that were identified as having so by the set of tests. Discussion: It was identified a consumer cognitive profile. One of the main conclusion of the present study was the verification of the insufficiency of MoCA for screening the cognitive state of individuals with addictive behaviours, making it, by this reason, aimed to be used paired up with a more extensive evaluation. It was concluded that a great percentage of the participants has cognitive impairments (confirming hypothesis 1) and that a brief cognitive assessment (MoCA) doesn’t appear to be sufficient to detect them efficiently, refuting in a certain manner the second hypothesis. It was verified, nevertheless, some interesting relations between MoCA and the set of tests, indicating the adequacy of MoCA for a first line of evaluation, which is an asset given the easiness of application (primarily given the duration of the test) and quick grading.